Impact of Integrated Farming System on Doubling Farmers’ Income - Ruikar B. A.; Gaikawad A. B.; Kharge A. P.; Kadam J. R.; Maske K. V. (Archives of Current Research International, 2024)
The present study was undertaken with the main objective impact of integrated farming system on doubling farmers’ income. The study was conducted in four district of Konkan region of Maharashtra namely Ratnagiri, Sindhudurg, Raigad and Palghar district. In all 200 respondents were selected by using multi stage sampling techniques. The “Ex-Post-Facto” research design was used for conducting the study. The data were collected through the personal interview. The data collected were processed and statistically analyzed by using statistical technique like frequency, percentage, mean, standard deviation and chi square test. The analysis of data revealed that majority (104.00 per cent) change percent in income was occurred in agriculture + dairy farming system followed by agriculture + horticulture + fishery (85.00 per cent), agriculture + poultry (82.00 per cent),agriculture + horticulture + poultry + dairy (84.00 per cent), agriculture + poultry (82.00 per cent), agriculture + Horticulture +poultry (76.00 per cent)agriculture +poultry + dairy (74.00 per cent) agriculture + horticulture + dairy (73.00 per cent), agriculture + poultry + goat rearing (66.00 per cent), agriculture+ horticulture + goat rearing (62.00 per cent), agriculture +poultry + goat rearing + horticulture (60.00 per cent), agriculture + goat rearing (58.00 per cent) and agriculture + dairy + goat rearing (14.00 per cent).